ePortfolios in the teaching of music and other creative and performing arts in four Australian universities - Rowley, J.; Blom, D.; Bennett, Dawn (International Society for Music Education, 2014)
This paper presents findings on the influences of the use of ePortfolios on teaching in music and other creative and performing arts. It is based on a two-year project in four Australian universities in 2012-2013. Rather than concentrate on the effects of ePortfolios on students, it focuses on teachers and their responses to teaching through the use of ePortfolios. As each of the universities involved in this project has different types of degrees in these discipline areas, and different policies and uses for ePortfolio-based work, ways that teaching responds to ePortfolio use differ between them. To explain this, roles of ePortfolios and ways they are used in music and other creative and performing arts areas in each of the universities are explained. This is followed by comments from staff members using ePortfolios in their teaching; changes to teaching as a result of ePortfolio use are particularly noted. These comments are derived from semi-structured interviews with the staff members involved in each of the four institutions of the project. The results of the project indicate various ways in which teaching in music and other creative and performing arts is being influenced by incorporation of ePortfolios into university work. Specifically, these relate to changes in assessment procedures, rethinking by staff of ways of demonstrating the longitudinal nature of study in music and other creative and performing arts, the ability of ePortfolios to provide holistic views of university learning, and the significance to staff of ePortfolios as representation of the multiple identities that music students develop during their studies.